P245 A RARE CAUSE OF OVERESTIMATION OF PULMONARY PRESSURE BY ECHOCARDIOGRAPHY: WHEN HEMODYNAMICS RELIEVES ECHOCARDIOGRAPHY AND ECHOCARDIOGRAPHY EXPLAINS HEMODYNAMICS. (18th May 2022) - Caravita, S; Baratto, C; Curti, E; Villella, F; Sganzerla, P; Perego, G; Badano, L; Muraru, D; Parati, G
Abstract: Echocardiography is the gatekeeper of the diagnostic workflow of pulmonary hypertension (PH). However, it lacks precision, and right heart catheterization (RHC) may be needed in selected cases. A morbidly obese 47–year–old woman (BMI= 58 Kg/m2) with dyspnea NYHA II was referred to our Center after a high probability of PH was found at echocardiography, this latter performed as a routine assessment before bariatric surgery. Despite a suboptimal acoustic window, the tricuspid regurgitant jet profile was well–defined, with an estimated systolic pulmonary artery pressure (PAP) of 100 mmHg. There were no overt echocardiographic signs of left heart disease. During RHC, mean PAP was just above normal values, with filling pressures at the upper limit of normal (Figure 1 ), high cardiac index (3.6 L/min/m2) and normal pulmonary vascular resistance (1.4 WU). The echocardiographic estimate of high systolic PAP was explained by an intraventricular RV pressure gradient of about 100 mmHg (Figure 2 ). Oximetry ruled out a significant intracardiac shunt. Since resting hemodynamics did not explain the patient's symptoms, the patient pre–test probability of having heart failure with preserved ejection fraction (HFpEF) was intermediate–high, and PAWP was in a grey–zone. Accordingly, we performed an exercise RHC. The test eventually unmasked HFpEF, as witnessed by an abnormal increase of PAWP and LV end–diastolic pressure (Figure 1 panel C and D). Exercise capacity was mildly reduced (71% of predicted) due to peripheral limitation with normal cardiac and respiratory reserves. Transesophageal echocardiography was then performed. It showed a muscular obstruction below the infundibulum dividing the RV into a high–pressure apical portion and a low–pressure infundibulum (Figure 3 ). This rare congenital anomaly was also associated with a restrictive perimembranous ventricular septal defect. Double–chambered RV has been reported to present rarely in adults, but it might be a cause of false Doppler echocardiographic estimate of PAP. Based on a meticulous invasive hemodynamic characterization at rest and during exercise, integrated with cardiovascular imaging, we could perform such a diagnosis. This congenital anomaly did not fully explain the patient's symptoms, which may better be attributed to cardiovascular complication of obesity (HFpEF). Accordingly, we referred the patient for bariatric surgery first, postponing the indication to cardiac surgery during the follow–up.